Pengaruh Knowledge Sharing Terhadap Agilitas Organisasi - Nova, Suherlan; Raharso, Sri (POLITEKNIK NEGERI BANDUNG, 2016)
Human resources is a basic and essential element to support the advancement and success of the organization. In supporting the progress and success of the organization, each component must be communicated in order to share information and knowledge needed. This study aims to determine how the process of sharing information and knowledge (knowledge sharing) to achieve the agility or agility required by organizations to compete with other organizations. This research is devoted to identifying the process of sharing information and knowledge in PT Nikkatsu Electric Work. To answer the goals described earlier, this study used quantitative research methods with descriptive analysis, correlation analysis and hypothesis testing using F test and subsequent T This research also analyzes the goals set by using regression analysis and coefficient of determination. Based on the research that has been done, regression equation of Y = 39.985 + 3,260X. The study states that there is a positive relationship between knowledge sharing and organizational agility in PT. Nikkatsu Electric Work at 0.582 and knowledge sharing affect organizational agility 33.8%.